Pelaksanaan Peraturan Daerah PELAKSANAAN PERATURAN DAERAH KABUPATEN MAGETAN NOMOR 1 TAHUN 2016 TENTANG PENGOLAHAN SAMPAH ORGANIK DENGAN SISTEM PENGOMPOSAN: PELAKSANAAN PERATURAN DAERAH KABUPATEN MAGETAN NOMOR 1 TAHUN 2016 TENTANG PENGOLAHAN SAMPAH ORGANIK DENGAN SISTEM PENGOMPOSAN - Harianto harianto; Zulin Nurcahayati (Universitas Merdeka Madiun, 2022)
Abstract. The purpose of the study was to determine the implementation of the Magetan Regency Regional Regulation Number 1 of 2016 concerning Organic Waste Processing with a Composting System. The population in the study included the Head of the Magetan Regency Environmental Service, the Head of the Hygiene Section, janitors and the community, totaling 100 people. Data collection techniques using questionnaires, observation and documentation. While the data analysis used quantitative descriptive analysis. The results of the study indicate that the implementation of the Waste Management Policy based on the Magetan Regency Regulation Number 1 of 2016 concerning Organic Waste Processing with a Composting System can be categorized as very good. keywords: local regulations, organic waste, composting